2022
DOI: 10.3389/fonc.2022.938749
|View full text |Cite
|
Sign up to set email alerts
|

An Emergent Role for Mitochondrial Bioenergetics in the Action of Snake Venom Toxins on Cancer Cells

Abstract: Beyond the role of mitochondria in apoptosis initiation/execution, some mitochondrial adaptations support the metastasis and chemoresistance of cancer cells. This highlights mitochondria as a promising target for new anticancer strategies. Emergent evidence suggests that some snake venom toxins, both proteins with enzymatic and non-enzymatic activities, act on the mitochondrial metabolism of cancer cells, exhibiting unique and novel mechanisms that are not yet fully understood. Currently, six toxin classes (L-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 147 publications
0
2
0
Order By: Relevance
“…Finally, Pic-III is the first of the SVMPs reported with action on mitochondrial bioenergetics. Emergent evidence suggests that several snake venom toxin classes (e.g., phospholipases [ 92 , 109 ], thrombin-like enzymes [ 28 ], three-finger toxins [ 110 , 111 ]) act on the mitochondrial bioenergetics [ 3 ], exhibiting unique and novel mechanisms that are not yet fully understood. This highlights the mitochondrion as an essential player in the snake venom action that requires more studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, Pic-III is the first of the SVMPs reported with action on mitochondrial bioenergetics. Emergent evidence suggests that several snake venom toxin classes (e.g., phospholipases [ 92 , 109 ], thrombin-like enzymes [ 28 ], three-finger toxins [ 110 , 111 ]) act on the mitochondrial bioenergetics [ 3 ], exhibiting unique and novel mechanisms that are not yet fully understood. This highlights the mitochondrion as an essential player in the snake venom action that requires more studies.…”
Section: Discussionmentioning
confidence: 99%
“…Snake venoms are a natural source of active proteins, also known as toxins, with enzymatic (metalloproteinases, serineproteinases, phospholipases A2, and L-amino oxidases) or non-enzymatic (neurotoxins, disintegrins, C-type lectins, cytotoxins, myotoxins, and cardiotoxins) activities. Several of these toxins are multifunctional and may act on multiple protein targets of their preys, which are highly specific to disrupt several biological processes in human cells, including cancer cells [ 1 , 2 , 3 , 4 ]. A plethora of studies on human envenoming has shown the functional diversity of snake toxins [ 1 , 5 ]; however, molecular mechanisms of action of several of these biomolecules remain poorly studied.…”
Section: Introductionmentioning
confidence: 99%